"I can only trust a friend”:Exploring managers’ enactment of favouritism in the workplace - Carnaz, A.; Duarte, H.; Ofela Palermo (Annual 15th EURAM Conference, 2015)
This paper aims to theoretically account for managers’ favouritism choices in the workplace. For achieving this objective, it explores the contingencies influencing the enactment of this behaviour, and the impact of ethical orientations on the way managers make sense of it. An inductive approach is adopted, for the generation of theory and frame the study within a comparative case study design. The semi-structured interview to managers was the key data collection method. Findings suggest that managers attribute a negative connotation to favouritism and, in turn, they enact it when others cannot hold them directly accountable for its consequences. Favouritism emerges as an aspect that can strengthen social relationships and networks, a quality that makes it an ‘attractive’ prospect to managers. When illustrating favouritism, managers appeal to friendship, and empathy adjusting their perceptions of fairness in order to pre-empty their behaviours of any intentionality. This research contributes to extant literature on favouritism by shedding light on how this phenomenon is enacted through managers’actions and discourses.